A comprehensive study of medically serious suicide attempts in France: incidence and associated factors. (10th January 2023) - Corbé, J.; Montout, C.; Fares, A.; Belhadj, I.; Boudemaghe, T.; Mura, T.; Lopez-Castroman, J.
Abstract: Aims: People who make medically serious suicide attempts (MSSAs) share a number of features with those who die by suicide, and are at a high risk of suicide themselves. Studies to date have mostly focused on clinical samples of MSSAs. An epidemiological examination at a national level can help to identify risk profiles and pathways of care in this population. Methods: We explored the French nationwide hospital discharge database (Programme de Médicalisation des Systèmes d'Information, PMSI) to identify any MSSA taking place between 2012 and 2019. Relevant demographic and medical information was collected about the first MSSA of each attempter. Data from 2010 and 2011 were used to verify the absence of prior attempts. Results: First occurrences of MSSAs amounted to 81 959 cases over 8 years, with a mean age of 45.8 years, and 53.6% women. Incidence was higher in women (18.1 v . 17.3 per 1 00 000). The most common suicide method was deliberate self-poisoning (64.9% of cases). In comparison, violent methods associated higher mortality and comorbidity and were more frequent in men. The most common mental disorders were mood disorders (55.6%) and substance use disorders (46.2%). A minority of MSSA survivors were hospitalised in psychiatry (32.5%), mostly women. Conclusions: MSSAs are frequent and easy to identify. There is a need to reinforce the continuity of psychiatric care for this population given the high risk of subsequent suicide, and the low rates of psychiatric hospitalisation after an MSSA even if violent methods are used. Specific care targeting this population could reduce treatment gaps.